Eco-friendly cellular phase microextraction technique based on the use of green microalgae cells for trace thallium species determination in natural water samples - Escudero, Leticia Belén (2015)
A simple and environmentally-friendly technique named cellular phase microextraction (Cell-PME) was developed for thallium (Tl) species determination. Basically, Tl(III) species was mixed with a solution containing Chlorella vulgaris microalgae cells (480 mg L-1) at pH 7 and the resulting system was stirred with a vortex for 8 min. After a centrifugation process, the sediment phase was directly injected into the graphite furnace of an electrothermal atomic absorption spectrometer. In contrast to Tl(III), Tl(I) species was not retained by the biomass. Optimization of variables influencing biosorption process, including sample pH, microalgae mass and sample volume, was performed. A biosorption efficiency of 65% and an enrichment factor of 50 were obtained with only 5.00 mL of sample. The limit of detection (LOD) was 8.3 ng L-1 Tl, while the relative standard deviation (RSD) was 5.1% (at 1 µg L-1 Tl and n = 10), calculated from the peak height of absorbance signals (Gaussian-shape and reproducible peaks). The proposed method was successfully applied to determine Tl species in environmental samples, including drinking and natural water. To the best of our knowledge, a biosorption process is applied for the first time for Tl species separation and determination in the analytical field.